Reputation
964
Top tag
Next privilege 1,000 Rep.
Create new tags
Badges
4 15
Impact
~27k people reached

  • 0 posts edited
  • 0 helpful flags
  • 164 votes cast
Jul
23
comment Show that $(A ∩ B) ▵ C = (A ▵ C) ▵ (A \setminus B)$
Thank you very much! That would be great! Take the time you need, I'm not in a hurry :)
Jul
23
accepted Show that $(A ∩ B) ▵ C = (A ▵ C) ▵ (A \setminus B)$
Jul
22
comment Show that $(A ∩ B) ▵ C = (A ▵ C) ▵ (A \setminus B)$
Hi Daniel. It is from the book "How to prove it". The question said that I could prove the equality by any method, Venn diagrams was a bit easy so I thought about using logical connectives instead.
Jul
22
comment Show that $(A ∩ B) ▵ C = (A ▵ C) ▵ (A \setminus B)$
Thank you for your comment @TerraHyde , if you have time I would love to see how you would do the development using set operations.
Jul
22
comment Show that $(A ∩ B) ▵ C = (A ▵ C) ▵ (A \setminus B)$
Hahaha thank you! Not exactly the kind of answer I was looking for but this is a good method to know about.
Jul
22
revised Show that $(A ∩ B) ▵ C = (A ▵ C) ▵ (A \setminus B)$
edited body
Jul
22
asked Show that $(A ∩ B) ▵ C = (A ▵ C) ▵ (A \setminus B)$
Jul
21
comment Understanding implication in logic truth tables (excerpt from textbook)
Thank you for the explanation! Much appreciated!
Jul
21
accepted Understanding implication in logic truth tables (excerpt from textbook)
Jul
20
comment Understanding implication in logic truth tables (excerpt from textbook)
Thanks for your answer! This is not how I understand the question. To me they are saying that if we make $P \implies Q$ false, the we don't need to look at $P$ and we can see that $Q$ is true by looking at line $2$ and $4$... I don't understand the logic in this...
Jul
20
asked Understanding implication in logic truth tables (excerpt from textbook)
Jun
16
accepted Can I simplify: $(¬P ∧ Q) ∨ (P ∧ ¬Q)$?
Jun
16
comment Can I simplify: $(¬P ∧ Q) ∨ (P ∧ ¬Q)$?
Thank you for your answer! This misunderstanding of the associativity rule was clearly my mistake. Thank you for pointing that out. Much appreciated.
Jun
16
comment Can I simplify: $(¬P ∧ Q) ∨ (P ∧ ¬Q)$?
It was meant to imply equivalence, sorry for the confusion.
Jun
16
comment Can I simplify: $(¬P ∧ Q) ∨ (P ∧ ¬Q)$?
Thank you for your comments! Ok I understand, but then information was lost along the way... I didn't think using the rules would be "destructive"... Clearly something I have not understood :)
Jun
16
comment Can I simplify: $(¬P ∧ Q) ∨ (P ∧ ¬Q)$?
Hmm I don't understand, am I using the associativity and tautology rules incorrect?
Jun
16
revised Can I simplify: $(¬P ∧ Q) ∨ (P ∧ ¬Q)$?
edited title
Jun
16
comment Can I simplify: $(¬P ∧ Q) ∨ (P ∧ ¬Q)$?
Hi, I am just trying to see if I can simplify the original statement.
Jun
16
revised Can I simplify: $(¬P ∧ Q) ∨ (P ∧ ¬Q)$?
added 3 characters in body; edited title
Jun
16
asked Can I simplify: $(¬P ∧ Q) ∨ (P ∧ ¬Q)$?